Great adaptations : star-nosed moles, electric eels, and other tales of evolution's mysteries solved - Catania, Kenneth, 1965- (Princeton University Press, 2020)
From star-nosed moles that have super-sensing snouts to electric eels that paralyze their prey, animals possess unique and extraordinary abilities. In Great Adaptations, Kenneth Catania presents an entertaining and engaging look at some of nature's most remarkable creatures. Telling the story of his biological detective work, Catania sheds light on the mysteries behind the behaviors of tentacled snakes, tiny shrews, zombie-making wasps, and more. He shows not only how studying these animals can provide deep insights into how life evolved, but also how scientific discovery can be filled with adventure and fun.